High-Level Structures Supporting the Institutional Framework for Foreign Direct Investment Promotion - Reichel, Marc (Other papers, 2022)
This note describes the options available to governments for establishing high-level institutional structures that can be used to improve the performance of their institutional framework for foreign investment promotion. The note discusses the context in which each of the options presented may be the best response to a specific problem or need. The note analyses the features, conditions, and strengths of five high-level institutional structures that can help improve the performance of the institutional framework for investment promotion: Investor Roundtables, Investment Councils, Ministerial Committees, IPA Boards, and Expert Commissions. The note summarizes the ability of each institution type to improve institutional coordination, enhance performance, provide insight, and deliver in-depth knowledge, and it describes the features of each. The note concludes that high-level institutional structures can address the underperformance of the institutional framework for foreign investment promotion when the cause has been duly identified, the strengths of the selected high-level structure match the cause of the problem, the setup follows international good practice, and the selection is based on consultations with private sector and effective interdepartmental coordination. Finally, the note acknowledges that the research on high-level structures is at an early stage and encourages further research of the topic